Southeast Asia in the new international era - Dayley, Robert; Neher, Clark D. (Boulder, CO : Westview Press, 2010)
From the Publisher: The fifth edition of Southeast Asia in the New International Era highlights the dramatic political events sweeping the region in the first decade of the twenty-first century. Where economic boom and crisis dominated events in the 1990s, political development and instability defines much of the region today. The promise of democracy in Thailand continues to slide amidst the forces of populism, military coup d'etat, constitutional crisis, and the politicization of the judiciary. Political freedom in Indonesia, by contrast, charts new territory as young democratic institutions strengthen. Vietnam's single-party rule delivers ongoing economic promise at the cost of political liberalization while the politics of patronage inhibits Cambodia's overall development. Burma's military regime maintains its grip on power by suppressing political opponents and Malaysia keeps communalism at bay while its long-standing parliamentary majority appears increasingly fragile. In the Philippines, the patterns of personalism, corruption, and elite rule plague democratic political development while Singapore's stable corporatist state stands in contrast to the struggling government of newly formed Timor-Leste. Occurring even as the U.S. War on Terror and China's rise creates new challenges, these changes and others are analyzed in this new fifth edition.
6: Singapore -- Map of the Singapore -- Institutions and social groups -- Democratization -- Economic development -- Singaporean state -- Foreign policy -- Conclusion -- Notes -- Resource guide -- 7: Brunei -- Map of the Brunei -- Institutions and social groups -- Democratization -- Economic development -- Bruneian state -- Foreign policy -- Conclusion -- Notes -- Resource guide -- 8: Burma -- Map of the Burma -- Institutions and social groups -- Democratization -- Economic development -- Burmese state -- Foreign policy -- Conclusion -- Notes -- Resource guide -- 9: Vietnam -- Map of the Vietnam -- Institutions and social groups -- Democratization -- Economic development -- Vietnamese state -- Foreign policy -- Conclusion -- Notes -- Resource guide -- 10: Cambodia -- Map of Cambodia -- Institutions and social groups -- Democratization -- Economic development -- Cambodian state -- Foreign policy -- Conclusion -- Notes -- Resource guide -- 11: Laos -- Map of the Loas -- Institutions and social groups -- Democratization -- Economic development -- Lao state -- Foreign policy -- Conclusion -- Notes -- Resource guide -- 12: Timor-Leste -- Map of the Timor-Leste -- Institutions and social groups -- Democratization -- Economic development -- Timor-Leste state -- Foreign policy -- Conclusion -- Notes -- Resource guide -- Southeast Asia: select indicators -- Index.
Rev. ed. of: Southeast Asia in the new international era / Clark D. Neher. 4th ed. 2002.
economic&political bookfair2015
Includes bibliographical references and index.
Keywords: Southeast Asia -- Politics and government -- 1945-; Southeast Asia -- Politics and government -- 21st century; Southeast Asia -- Foreign relations